Analysis Of Sharia Economic Law On Platet-Rich Plasma (PRP) Services In Beauty Clinics - Mariani; Erry Fitrya Primadhany; Rabiatul Adawiyah; Tutik Aminah; Fathur Baldan Haramain (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Purpose : This study aims to analyze the practice of Platelet-Rich Plasma (PRP) treatment in beauty clinics from the perspective of Sharia economic law. The research specifically examines how PRP services align with Islamic legal principles, particularly in relation to consumer protection, transparency, and ethical business practices in the beauty industry. Design/Method/Approach : The research employs a qualitative case study approach by conducting field observations and semi-structured interviews with practitioners and clients at Bening’s Beauty Clinic in Palangka Raya. The legal analysis is supported by the framework of Islamic jurisprudence (fiqh muamalah), Indonesian consumer protection law, and secondary literature on Islamic economic ethics. Findings : The results indicate that PRP services provide significant aesthetic benefits, yet their implementation raises issues regarding risk communication and informed consent. While the procedures meet medical standards, the lack of detailed disclosure on possible side effects and treatment limitations creates information asymmetry between providers and patients. From a Sharia perspective, this condition may conflict with the principles of akad yang sahih, gharar (uncertainty), and maslahah (public benefit). Strengthening transparency and consumer education is therefore essential to ensure compliance with Sharia economic law. Originality/Values : This study contributes to the growing discourse on Islamic law and contemporary health-beauty practices by offering a contextual analysis of PRP treatment within Sharia economic law. It highlights the need for an integrative model that harmonizes medical protocols, consumer rights, and Islamic ethical principles. The findings are valuable for policymakers, clinic management, and scholars in developing Sharia-compliant standards for beauty services.